Organocatalytic Enantioselective [4+3]‐Cycloadditions of Azaoxyallyl Cations with 2‐Aminophenyl Enones. Issue 17 (1st August 2021) - Lee, Chang Yoon; Kwon, Yong Il; Jang, Hyun Sun; Lee, Sumin; Chun, Yoo Lim; Jung, Junyang; Kim, Sung‐Gon
Abstract: The first organocatalytic asymmetric [4+3]‐cycloaddition of 2‐aminophenyl α, β‐unsaturated carbonyls with in situ generated azaoxyallyl cations was developed, and enantioenriched functionalized seven‐membered 1, 4‐benzodiazepine‐3‐ones were obtained in good yields and with excellent enantioselectivities. This approach was also extended to the first asymmetric [4+3]‐cycloaddition of δ‐hydroxy α, β‐unsaturated carbonyls, affording 1, 4‐oxazepanes in one step under mild conditions. Several of the novel adducts demonstrated promising bioactivity in the prevention of peripheral nerve degeneration. Abstract :